Phylogenic evolution of beat perception and synchronization: a comparative neuroscience perspective - Huang, Jin-Kun; Yin, Bin (Frontiers in Systems Neuroscience, 2023)
The study of music has long been of interest to researchers from various disciplines. Scholars have put forth numerous hypotheses regarding the evolution of music. With the rise of cross-species research on music cognition, researchers hope to gain a deeper understanding of the phylogenic evolution, behavioral manifestation, and physiological limitations of the biological ability behind music, known as musicality. This paper presents the progress of beat perception and synchronization (BPS) research in cross-species settings and offers varying views on the relevant hypothesis of BPS. The BPS ability observed in rats and other mammals as well as recent neurobiological findings presents a significant challenge to the vocal learning and rhythm synchronization hypothesis if taken literally. An integrative neural-circuit model of BPS is proposed to accommodate the findings. In future research, it is recommended that greater consideration be given to the social attributes of musicality and to the behavioral and physiological changes that occur across different species in response to music characteristics.